STUDY OF FEMINISM ARCHITECTURE CONCEPT IN MUSEUM BUILDING "THE SOLOMON R GUGGENHEIM MUSEUM IN AMERICA US" - Afied Dien Haqsaleh; Ashadi Ashadi (Journal of Development and Integrated Engineering, 2021)
Abstract: A study of the concept of feminist architecture in the Solomon R Guggenheim Museum building. In the past, an understanding held by society regarding sex differences between men and women affected control, where women were not given freedom, power and rights completely different from men who could do anything and be anything. In the world of architecture, feminism is present as part of post-modern architecture because of the saturation of modern buildings that occur. studies the concept of Feminist Architecture at the Solomon R Guggenheim Museum in New York, America, which is considered to have approached the principles of feminist architecture in its buildings and the method to be used is descriptive qualitative. The author needs to do research on the concept of Feminism Architecture in order to know its true characteristics. From the research results, it is concluded that the case study of the building that has been studied is the Feminist Architecture approach and applies it and among them is having the form of a building that resembles the shape of items used by women, the shape of the building has arches reflecting the woman's body, there is a division of space as a divider between women and men, as well as the use of colors in buildings or interiors that match the preferences of women. Keywords: Architecture, Architecture Feminism, Feminism, Solomon R Guggenheim Museum, Women.